A randomized, open-label study to investigate the effect of belimumab on pneumococcal vaccination in patients with active, autoantibody-positive systemic lupus erythematosus. (December 2017) - Chatham, W; Chadha, A; Fettiplace, J; Kleoudis, C; Bass, D; Roth, D; Gordon, D
Objective: Intravenous belimumab 10 mg/kg is approved as an add-on therapy in patients with active, autoantibody-positive systemic lupus erythematosus. This study aimed to assess the impact of belimumab on immune response to pneumococcal vaccination in patients with systemic lupus erythematosus. Methods: This was a Phase 4, open-label study (GSK BEL115470; NCT01597492) conducted in the United States. Patients were randomized (7:9) to receive a 23-valent pneumococcal vaccination four weeks prior to (pre-belimumab cohort) or 24 weeks after (belimumab-concurrent cohort) commencing four-weekly belimumab 10 mg/kg intravenous treatment plus standard systemic lupus erythematosus therapy. Analyses of vaccine titers were performed on the as-treated population (received ≥1 dose of belimumab). The primary endpoint was the proportion of patients with positive antibody responses (≥2-fold increase from pre-vaccination levels, or post-vaccination level ≥ 0.6 µg/mL if pre-vaccination levels were unquantifiable) to ≥1 of 23 pneumococcal vaccine serotypes, four weeks post vaccination. Other endpoints included the proportion of patients with positive antibody responses to ≥2 to ≥10, and ≥11–23 (post hoc analysis) of serotypes. Safety was assessed by monitoring adverse events. Results: Seventy-nine patients received pneumococcal vaccination (pre-belimumab cohort, n = 34; belimumab-concurrent cohort, n = 45). The majority (87.3% [69/79]) completed the study; 10 (12.7%) withdrew (patient request, n = 3; adverse event, n = 3; lost to follow-up, n = 2; other, n = 2). At Week 4 post-vaccination, 97.0% (32/33) and 97.6% (40/41) of patients (pre-belimumab and concurrent belimumab cohorts, respectively) had a positive response to ≥1 of 23 pneumococcal serotypes. Over 85% of patients in both cohorts responded to ≥10 of serotypes, approximately 80% responded to ≥12 serotypes, and approximately two-thirds responded to ≥16 serotypes. Little difference was observed between cohorts across a broad response, up to 23 serotypes. Eight (23.5%) patients experienced an adverse event considered by the investigator to be treatment-related in the pre-belimumab cohort and four (8.9%) in the belimumab-concurrent cohort; seven patients experienced non-fatal serious adverse events (pre-belimumab cohort, 11.8% [ n = 4]; concurrent-belimumab cohort, 6.7% [ n = 3]), and no deaths were reported. Conclusion: The proportion of patients generating a response to ≥1 pneumococcal serotype did not differ between the pre-belimumab and belimumab-concurrent cohorts; the proportions were also comparable across a broader response (from ≥2 serotypes to 23 serotypes).